2005
DOI: 10.1063/1.1890465
|View full text |Cite
|
Sign up to set email alerts
|

Polarized transmission spectra of the fiber-microsphere system

Abstract: The polarized transmission spectra of a fiber-microsphere system was investigated. Light from an optical fiber was side coupled into the dielectric microsphere through optical tunneling. It was found that the polarization of some of the light coupled into the microsphere and back into the fiber changed by 90°. The experiments showed a level of high signal-to-noise ratio peaks at the resonant frequencies in the polarized spectra and the possibility of discriminating between TE and TM modes of the microsphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…(Our coupled-mode-theory calculations of the strength of outcoupling to the orthogonal polarization, as proposed in Ref. [10], rule it out as being too weak to produce the observed effect.) The likelihood of observation of CPC effects depends on the mode density, but under some conditions as many as 30% of the pumped modes produce significant throughput in the orthogonal polarization.…”
Section: Observations and Implicationsmentioning
confidence: 91%
See 1 more Smart Citation
“…(Our coupled-mode-theory calculations of the strength of outcoupling to the orthogonal polarization, as proposed in Ref. [10], rule it out as being too weak to produce the observed effect.) The likelihood of observation of CPC effects depends on the mode density, but under some conditions as many as 30% of the pumped modes produce significant throughput in the orthogonal polarization.…”
Section: Observations and Implicationsmentioning
confidence: 91%
“…In early work on strain tuning, TE-TM anticrossing was observed and attributed to impurity-enhanced birefringence [6]. In a more recent observation with a tapered-fiber-coupled microsphere [10], the proposed explanation for throughput of the orthogonal polarization was a nonzero outcoupling overlap integral between the excited WGM and the nominally orthogonal fiber mode. Resolution of the disagreement between these two proposed explanations of CPC is one part of the overall goal of the work to be presented here.…”
Section: Cross-polarization Mode Couplingmentioning
confidence: 96%
“…Recent reports have shown a further step, taking into account the difference between modes with different polarizations in microspheres. In particular, changes in the output polarization after coupling into the resonator have been observed 16 and transverse electric (TE) and transverse magnetic (TM) modes have been discriminated 17 .…”
mentioning
confidence: 99%
“…Since excitation of WGMs on any microresonator are polarization sensitive, it is important to understand their performance under TE/TM launching conditions and their polarization cross-coupling. It has been reported that light can change its state of polarization when it is coupled into and out of a microcavity [7]. A polarimetric setup was used in order to control the polarization and characterize the polarization cross-coupling in microspheres [8].…”
Section: Introductionmentioning
confidence: 99%